2019
DOI: 10.2135/cropsci2018.12.0731
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cytogenetic Characterization of the Native Forage GrassTrichloris crinita

Abstract: Trichloris crinita (Lag.) Parodi is a perennial forage grass native to—and of wide distribution in—arid and semiarid regions of the American continent. In addition to its good forage quality, this species is particularly valued in these drylands due to its high tolerance to drought, salinity, trampling, and grazing. Genetic and cytogenetic information for T. crinita is very scarce, hindering progress in genetic research and breeding of the species. We describe chromosome numbers, karyotypes, heterochromatin di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 72 publications
0
5
0
2
Order By: Relevance
“…Los resultados obtenidos en el presente trabajo indican que todas las poblaciones evaluadas de T. crinita, tanto de Sudamérica como de Norteamérica, presentan similar contenido de ADN nuclear (2C entre 1,95 -2,01 pg), lo que sugiere la misma ploidía del ADN (Suda et al, 2006). La uniformidad que encontramos es consistente con evaluaciones realizadas sobre otras 20 poblaciones de T. crinita originarias del centro-oeste de Argentina, donde todas presentaron el mismo nivel de ploidía (2n = 4x = 40) (Kozub et al, 2019). Cabe destacar, que en el presente trabajo ampliamos la evaluación hacia poblaciones del sector disyunto norte de la distribución de la especie.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Los resultados obtenidos en el presente trabajo indican que todas las poblaciones evaluadas de T. crinita, tanto de Sudamérica como de Norteamérica, presentan similar contenido de ADN nuclear (2C entre 1,95 -2,01 pg), lo que sugiere la misma ploidía del ADN (Suda et al, 2006). La uniformidad que encontramos es consistente con evaluaciones realizadas sobre otras 20 poblaciones de T. crinita originarias del centro-oeste de Argentina, donde todas presentaron el mismo nivel de ploidía (2n = 4x = 40) (Kozub et al, 2019). Cabe destacar, que en el presente trabajo ampliamos la evaluación hacia poblaciones del sector disyunto norte de la distribución de la especie.…”
Section: Discussionunclassified
“…Uno de los aspectos básicos en la ecología de poblaciones de plantas nativas es conocer si existe variabilidad intraespecífica en el nivel de ploidía (Lučanová, 2019). Recientemente, diferentes estudios citogenéticos combinando análisis de citogenética clásica y molecular realizados en 20 poblaciones argentinas de T. crinita han demostrado que las mismas presentan igual nivel de ploidía 2n = 4x = 40 (Kozub et al, 2019). No obstante, variaciones intraespecíficas en el nivel de ploidía han sido reportadas en la subfamilia Chloridoideae (De Silva y Snaydon, 1995;Nakagawa et al, 1987).…”
Section: Introductionunclassified
“…In the last decades, representative plants from natural populations of T. crinita and other native grasses were collected from the Monte phytogeographical region, located in the west of Argentina, and evaluated at various levels. These studies revealed broad genetic diversity for this germplasm collection at the DNA level (using AFLP and SSR molecular markers), as well as for morphological, cytological, physiological, agronomic and foragequality traits (Greco and Cavagnaro, 2005;Cavagnaro et al, 2006;Kozub et al, 2018a;Kozub et al, 2019;Dominguez et al, 2022). However, to date, no thorough evaluation of drought tolerance in the GBNG T. crinita collection has been performed.…”
Section: Introductionmentioning
confidence: 89%
“…In full agreement with this hypothesis, we previously found that molecular marker (AFLP)-based genetic clustering of these same T. crinita accessions was not associated with geographical origin or habitat conditions, and suggested that T. crinita natural populations were genetically heterogeneous (Cavagnaro et al, 2006). Further support for genetic heterogeneity in T. crinita natural populations comes from studies -using this same germplasm collection-reporting lack of association between geographical origin or aridity levels in the accessions collection sites and various morphometric and quantitative agronomic traits, including forage productivity (Cavagnaro et al, 2006) and nutritional quality (Dominguez et al, 2022), as well as karyotype and cytogenetic characterizations (Kozub et al, 2019). Presumably, differences in the number and nature of the plant materials analyzed (2-4 ecotypes or populations vs. 21 accessions derived from singleplant descendants), and the range of aridity in the original habitats (e.g., range for mean annual precipitation was 179-1142 mm in Marinoni et al (2020) vs. 104-519 mm in this work) may partially account for these discrepancies between previous works and the present study.…”
mentioning
confidence: 96%
“…Thus, in the last decades, plant samples from natural populations of L. crinita and other native grasses were collected from the Monte region and conserved, propagated, and evaluated at various levels at IADIZA. These studies revealed broad genetic diversity in L. crinita germplasm for morphological, cytological, physiological, and agronomic traits, including drought tolerance and forage biomass production, as well as extensive variation at the DNA level, evaluated by molecular markers analysis (Cavagnaro et al, 2006;Greco & Cavagnaro, 2003Kozub, Barboza et al, 2018;Kozub et, al., 2019). However, to date, little is known about the nutritive value of this species and its intraspecific variability.…”
Section: Crop Sciencementioning
confidence: 99%